Evaluation of soft tissue thicknesses of facial midline landmarks before and after puberty - Soosan Sadeghian; Arash Ghodousi; Roshanak Ghafari; Erfaneh Afsari; Peyman Raei (Isfahan University of Medical Sciences, 2011)
Introduction: In recent years, proportions and harmony of orofacial soft tissues have gained great importance in orthodontics. The aim of this research was to evaluate soft tissue thickness changes of facial midline landmarks during growth in both genders.Materials and methods: In this analytical-descriptive study, lateral cephalometric views of ninety-eight 6-18 year-old patients referring to the Orthodontics Department of Khorasegan Azad University were evaluated. The positions of 7 facial midline landmarks, including glabella, soft tissue nasion, soft tissue points A and B, soft tissue pogonion, and superior and inferior labrale, were determined and then the thicknesses of the landmarks were measured. Data was compared between two groups of under and above 12 years of age between males and females using independent t-test (α=0.05).Results: There were no statistically significant differences between the soft tissue thicknesses of both sexes in any of the landmarks except nasion (p value=0.026) and point B (p value=0.043) in the group under 12 years of age. Differences between the soft tissue thicknesses in both sexes over 12 years of age were statistically significant in nasion (p value = 0.043), point A (p value=0.001), and superior labrale (p value<0.001). Differences between soft tissue thicknesses of all the landmarks were statistically significant between the two age groups in males except point B (p value=0.119); however, in females only the thickness of soft tissue nasion (p value=0.105) and superior labrale (p value=0.968) were not statistically significant between the two age groups.Conclusion: Soft tissue thicknesses were almost the same in boys and girls except nasion and point B before puberty. After puberty upper face soft tissue thicknesses, including glabella and point A, were greater in boys compared to girls. However, in both sexes, soft tissue thicknesses of facial midline landmarks increased after 12 years of age. Key words: Soft tissue, Orthodontics, Radiography.